2022
DOI: 10.1002/trc2.12289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cerebrospinal fluid biomarkers associated with neurodegenerative diseases in healthy cynomolgus and rhesus macaque monkeys

Abstract: Monkeys are becoming important translational models of neurodegenerative disease. To facilitate model development, we measured cerebrospinal fluid (CSF) concentrations of key biomarkers in healthy male and female cynomolgus and rhesus macaques. Amyloid beta (Aβ40, Aβ42), tau (total tau [t‐tau], phosphorylated tau [pThr181]), and neurofilament light (NfL) concentrations were measured in CSF of 82 laboratory‐housed, experimentally naïve cynomolgus (n = 33) and rhesus (n = 49) macaques. Aβ40 and Aβ42 were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…While marmosets are increasingly used in studies of aging and neurodegeneration, rhesus and cynomolgus macaques, and African green monkeys are more widely used. CSF concentrations of T-tau, P-tau, and NfL were not correlated with age in cynomolgus macaques ( Macaca fascicularis ) or rhesus macaques (( Macaca mulatta), though the age range tested in this study was relatively narrow (2—12 years) and did not capture aged animals [ 16 ]. However, Aβ concentration was significantly correlated with age in vervet monkeys ( Chlorocebus aethiops sabaeus )[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While marmosets are increasingly used in studies of aging and neurodegeneration, rhesus and cynomolgus macaques, and African green monkeys are more widely used. CSF concentrations of T-tau, P-tau, and NfL were not correlated with age in cynomolgus macaques ( Macaca fascicularis ) or rhesus macaques (( Macaca mulatta), though the age range tested in this study was relatively narrow (2—12 years) and did not capture aged animals [ 16 ]. However, Aβ concentration was significantly correlated with age in vervet monkeys ( Chlorocebus aethiops sabaeus )[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Aβ concentration was significantly correlated with age in vervet monkeys ( Chlorocebus aethiops sabaeus )[ 4 ]. Robertson et al[ 16 ] reported rhesus macaques had higher concentrations of Aβ40 and Aβ42 compared to cynomolgus macaques, and female rhesus had higher concentrations of Aβ40 and Aβ42 than male rhesus. Rizzo et al [ 15 ] reported increases in plasma Aβ42 and an increase in plasma Aβ42:40 ratio in genetically engineered marmosets with targeted AD gene knock-ins relative to wild type controls.…”
Section: Discussionmentioning
confidence: 99%